2019
DOI: 10.1097/cmr.0000000000000549
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD163 expression and its correlation with cyclooxygenase-2 and vascular endothelial growth factor expression in cutaneous melanoma

Abstract: In several cancers, tumor progression is associated with the infiltration of tumor-associated macrophages (TAMs). The aim was to evaluate the prognostic significance of expression of CD163 and CD68 (TAMs’ markers) and their correlation with vascular endothelial growth factor (VEGF) and cyclooxygenase-2 (COX-2) expression in cutaneous melanoma. Diagnostic tissues from 102 patients of cutaneous melanoma were evaluated by immunohistochemistry for their CD68, CD163, VEGF, and COX-2 expression. Correlations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In our previous study, high CD163 expression was associated with lower OS, suggesting the prognostic significance of CD163 expression in cutaneous melanoma [16]. We observed that CD163 expression correlated with VEGF and COX-2 expression [16].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In our previous study, high CD163 expression was associated with lower OS, suggesting the prognostic significance of CD163 expression in cutaneous melanoma [16]. We observed that CD163 expression correlated with VEGF and COX-2 expression [16].…”
Section: Discussionsupporting
confidence: 49%
“…In our previous study, high CD163 expression was associated with lower OS, suggesting the prognostic significance of CD163 expression in cutaneous melanoma [16]. We observed that CD163 expression correlated with VEGF and COX-2 expression [16]. However, limited information is available about the expression of CD163 and its relationship with immune checkpoint molecules, particularly PD-1 and LAG-3.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The contrasting trends of CD68 + macrophages and CD163 + macrophages against Breslow depth is striking in suggesting a differential expression pattern, albeit with the former being non-significantly correlated. A recent study by Lee et al 29 provides corroborating evidence that increased CD163 + cell infiltration is associated with increased Breslow depth. 29 There is much evidence that tumours exert a strong polarising effect on recruited cells, and it remains to be determined whether the CD68 + and CD163 + infiltration is reflective of differential recruitment, or a system in which CD68 + cells are recruited and polarised to a CD163 + phenotype, which is less functionally active in the parameters we observed, such as arginase and iNOS activity and influencing gene expression within the tumour.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study by Lee et al 29 provides corroborating evidence that increased CD163 + cell infiltration is associated with increased Breslow depth. 29 There is much evidence that tumours exert a strong polarising effect on recruited cells, and it remains to be determined whether the CD68 + and CD163 + infiltration is reflective of differential recruitment, or a system in which CD68 + cells are recruited and polarised to a CD163 + phenotype, which is less functionally active in the parameters we observed, such as arginase and iNOS activity and influencing gene expression within the tumour. 30 32 This system would explain both the increased prevalence of CD68 + macrophages in less progressed tumours and increased accumulation of CD163 + macrophages in more advanced tumours.…”
Section: Discussionmentioning
confidence: 66%